The Interaction of Single Nucleotide Polymorphisms on Fibroblast Growth Factor 19 Superfamily Genes Is Associated With Alcohol Dependence-Related Aggression - Xu, Jinzhong; Wu, Fenzan; Wang, Fan; Yang, Fan; Liu, Meng; Lou, Mengbei; Wu, Linman; Li, Hui; Lin, Wenhui; Fan, Yunchao; Chen, Li; Liu, Yanlong; et al. (Frontiers in Genetics, 2021)
Alcohol dependence (AD) is characterized by compulsive alcohol consumption, which involves behavioral impairments such as aggression. Members of fibroblast growth factor (FGF) 19 superfamily, including FGF19, FGF21, and FGF23, are major endocrine mediators that play an important role in alcohol metabolism and alcohol related disorders. The objective of the present study is to explore the possible associations among the interaction of single nucleotide polymorphisms (SNPs) of FGF 19 superfamily, AD occurrence and aggression in patients with AD. A total of 956 subjects were enrolled in this study, including 482 AD patients and 474 healthy controls. Michigan Alcoholism Screening Test (MAST) was used to measure the level of AD, a Chinese version of the Buss-Perry Aggression Questionnaire was used to evaluate the aggressive behavior of subjects, and MassARRAY@ system was used to genotype rs948992 of FGF19, rs11665841 and rs11665896 of FGF21, rs7955866 and rs11063118 of FGF23. The results showed that AD patients presented a significantly higher level of aggression compared to healthy controls, and MAST scores were significantly positively associated Buss-Perry aggression scores (r = 0.402, p < 0.001) in AD patients. The interaction of FGF19 rs948992 TC × FGF21 rs11665896 GG presented the high-risk genotype combination predicting the high level of alcohol dependence. In addition, the interaction of FGF19 rs948992 TC × FGF21 rs11665896 TG × FGF23 rs11063118 TT presented the high-risk genotype combination predicting the high level of aggression in AD patients. Our results added evidence linking the combination of rs948992 TC × rs11665896 TG × rs11063118 TT to aggressive behavior in AD patients and pointed out the potential usefulness of the SNPs of FGF19 superfamily as a predictor for the aggression in AD patients.